Appetite for grass: Re‐engineering landscapes of Otago and Southland 1864–1914. (23rd July 2020) - Holland, Peter; Olson, Sherry
Abstract: Family farms of southern New Zealand, by effective integration of their biological engines—equine, ovine and bovine—sustained a rising productivity for half a century. In response to demand in the North Atlantic core, settlers on a South Pacific frontier were converting indigenous landscapes of tussock, scrub and wetland to introduced grasses. The comments that farmers entered to a daybook or reported to a journalist demonstrate a systems understanding. The changes in landscape and diet were part of a worldwide trend towards dependence on grass, recognized today as a source of severe environmental costs.